Human Factors for More Usable and Safer Health Information Technology: Where Are We Now and Where do We Go from Here? - Kushniruk, A.; Nohr, C.; Borycki, E. (Yearbook of Medical Informatics, 2016)
A wide range of human factors approaches have been developed and adapted to healthcare for detecting and mitigating negative unexpected consequences associated with technology in healthcare (i.e. technology-induced errors). However, greater knowledge and wider dissemination of human factors methods is needed to ensure more usable and safer health information technology (IT) systems.Objective: This paper reports on work done by the IMIA Human Factors Working Group and discusses some successful approaches that have been applied in using human factors to mitigate negative unintended consequences of health IT. The paper addresses challenges in bringing human factors approaches into mainstream health IT development.Results: A framework for bringing human factors into the improvement of health IT is described that involves a multi-layered systematic approach to detecting technology-induced errors at all stages of a IT system development life cycle (SDLC). Such an approach has been shown to be needed and can lead to reduced risks associated with the release of health IT systems into live use with mitigation of risks of negative unintended consequences.Conclusion: Negative unintended consequences of the introduction of IT into healthcare (i.e. potential for technology-induced errors) continue to be reported. It is concluded that methods and approaches from the human factors and usability engineering literatures need to be more widely applied, both in the vendor community and in local and regional hospital and healthcare settings. This will require greater efforts at dissemination and knowledge translation, as well as greater interaction between the academic and vendor communities.
Keywords: Human factors; usability; electronic health records; safety; error; human-computer interaction; technology-induced error